Computationally Effective Gravity Inversion Allows for High-Resolution Regional Density Modeling of Earth's Crust with the Inclusion of the Topography Layer - Martyshko Pyotr; Byzov Denis; Chernoskutov Aleksandr (Russian Journal of Earth Sciences, 2022)
The problem of inverting measured gravity data for large regions is of a great importance for planetary structure studies. Unfortunately, the usual methods of local gravity field inversion do not scale up well. There are three primary factors that start to play significant role: topography or terrain surface with large height differences, spherical geometry of the planet, and high computational complexity. In our previous work we were separately considering each of those problems in detail. In this paper however, we will address those issues simultaneously, offering a complete and computationally effective method of recovering spherical density model of Earth's crust with the upper topography layer. The method utilizes a closed form expression for the discretized model's gravity field which allows for great accuracy and speed without enforcing restrictions on model geometry or gravity field data grid. Inversion process is based on the conjugate gradient method. An example of inversion for a synthetic regional model is presented.